Peramalan Harga Emas di Kota Padang Menggunakan Metode Autoregressive Integrated Moving Average (ARIMA) - jannah, Ro'i khatul; Agustina, Dina (UNIVERSITAS NEGERI PADANG, 2025)
Gold is often chosen as an investment because of its profit potential. To maximize returns and avoid losses, it is important for investors to understand the volatile movement of gold prices. This research aims to forecast gold prices using the Autoregressive Integrated Moving Average (ARIMA) method. ARIMA is an effective method for stationary and non-stationary data, with p, d, and q parameters representing the main components: Autoregressive, differencing, and Moving Average. From this research, the best model ARIMA (0, 1, 1) was obtained. The forecasting results show that the price of gold in January 2024 is Rp990,324.8 and February 2024 is Rp997,035.8, which shows an increase in price with the accuracy of the model using MAPE of 6.72%, meaning that the model is in a very good category according to the MAPE <10% criteria.